2018
DOI: 10.1080/00952990.2017.1420795
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic analysis of opioid dependence treatment dose and dropout rate

Abstract: This study suggests that functional polymorphisms related to synaptic dopamine or serotonin levels may predict dropout rates during methadone treatment. Patients with the S/S genotype at 5-HTTLPR in SLC6A4 or the Val/Val genotype at Val158Met in COMT may require additional treatment to improve their chances of completing addiction treatment. Replication in other methadone patient populations will be necessary to ensure the validity of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Genetic variation impacting pharmacokinetics and pharmacodynamics for buprenorphine will likely be important for treatment outcomes, although there is no published research identifying polymorphisms associated with buprenorphine dose or serum concentration [36]. There have been some studies of the pharmacogenetics of buprenorphine efficacy, implicating OPRD1, SLC6A3, SLC6A4, and COMT; however, far more research must be done in larger sample sizes for further discovery [23,24,37,38]. There is also the unexplored area of the pharmacogenomics of adverse reactions to buprenorphine [36].…”
Section: Improving Successful Opioid Substitution Therapymentioning
confidence: 99%
“…Genetic variation impacting pharmacokinetics and pharmacodynamics for buprenorphine will likely be important for treatment outcomes, although there is no published research identifying polymorphisms associated with buprenorphine dose or serum concentration [36]. There have been some studies of the pharmacogenetics of buprenorphine efficacy, implicating OPRD1, SLC6A3, SLC6A4, and COMT; however, far more research must be done in larger sample sizes for further discovery [23,24,37,38]. There is also the unexplored area of the pharmacogenomics of adverse reactions to buprenorphine [36].…”
Section: Improving Successful Opioid Substitution Therapymentioning
confidence: 99%
“…Data from the randomized clinical trial Starting Treatment With Agonist Replacement Therapies (START), has been used to perform several pharmacogenomic analyses of OUD treatment outcomes [ 44 ] . Genotypic information was available for 60% ( n = 764/1,267) of the patient population, which was primarily composed of European Americans ( n = 599), with few African Americans ( n = 79) and other ethnicities ( n = 96) [ 29 ] . Over a 24-week period, participants treated with methadone ( n = 364, 66% male) or buprenorphine/naloxone ( n = 410, 71% males) were submitted to weekly urine drug screens.…”
Section: Pharmacogenes: Opioid Receptorsmentioning
confidence: 99%
“…Social determinants of health such as housing status, involvement with the criminal justice system, and socioeconomic status may also impact treatment outcomes [ 4 , 27 , 28 ] . Lastly, genetic variations can alter pharmacological effects and influence therapeutic response [ 29 – 31 ] . Pharmacogenomic studies evaluate genotypic-phenotypic associations and their potential impact on pharmacokinetic (e.g., metabolic function, dosing requirements) and pharmacodynamic (e.g., receptor activity, treatment efficacy) parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Various in vitro and in vivo studies have shown the involvement of different cytochrome P450 (CYP) enzymes, particularly CYP2B6, in methadone metabolism, associated with the CYP2B6‐G516T genetic polymorphism and, to a lesser extent, CYP2D6, CYP3A4, and the gene encoding ATP Binding Cassette Subfamily B Member 1 ( ABCB1 , the permeability glycoprotein [P‐gp] transporter) . The influence of genetic polymorphisms on pharmacodynamic properties and treatment response has been less explored, and is not supported by much evidence . Moreover, the impact of genetic variations could be compounded by interactions between many environmental and individual factors …”
Section: Introductionmentioning
confidence: 99%
“…The results of pharmacogenomics studies in the field of methadone maintenance treatment (MMT) have been described in terms of dose magnitude, plasma or dose‐adjusted plasma concentrations, responders vs nonresponders, and adverse effects. In these previous studies, the response to treatment was defined by the dose requirement, continued opioid use or composite criteria, including the nonconsumption of heroin and cocaine, the absence of complaints of withdrawal symptoms, the steady and regular attendance at the therapy programme, dropout rate and mean dose …”
Section: Introductionmentioning
confidence: 99%